Application Of The Problem Based Learning Model To Improve Student Learning Outcomes In Class VII Of SMP Negeri 8 Kei Besar On Animal Classification Material - Yosefa Rahayaan; Jefry J. Mamangkey; Carolin Manuahe (Asosiasi Riset Ilmu Matematika dan Sains Indonesia, 2024)
Problem-based learning is an educational approach that centers around the exploration of real-world problems, with an emphasis on finding genuine solutions through realistic investigation. The objective of this study is to ascertain the outcomes of students' learning achievement through the implementation of a problem-based learning approach, specifically focusing on the topic of animal classification. This study employs the methodology of classroom action research. The research was conducted at SMP Negeri 8 Kei Besar. The participants of the study consisted of 33 pupils in the seventh grade. The research findings indicated that the rate of classical learning achievement in the first cycle was 27%, with a mean score of 62%, while in the second cycle it increased to 81.9%, with an average score of 76%. The findings of this study demonstrate that the utilization of a problem-based learning approach in teaching animal classification can enhance students' academic achievements.